High‐viscosity polyalkylphenanthrene oils: Synthesis and evaluation of lubricating properties. (8th June 2022) - Cui, Jingze; Tang, Qiong; Chen, Chen; Xu, Hong; Liu, Lei; Dong, Jinxiang
Abstract: Producing lubricating base oils from coal‐based chemicals is an alternative route for replacing the conventional petro‐based lubricants. Herein, we firstly reported the synthesis of high‐viscosity polyalkylphenanthrene oils derived from the coal‐based chemicals (phenanthrene, C6/C8‐olefins) by alkylation with acidic ionic liquid (Et3 NHCl∙2AlCl3 ) as catalyst. Their primary physicochemical properties were studied in detail to reveal their structure–property relationships, the existence of the phenanthrene ring in their molecular structure led to some good property, such as high‐kinematic viscosity (12.6–30.2 mm 2 ·s −1 at 100°C), better flash point (>230°C), high‐oxidative onset time (>230°C) and good polarity. Moreover, the tribological performances of the synthetic oils and the commercial PAO‐20 lubricating base oil were studied for comparison, these alkylated phenanthrenes, especially PHP‐3 and POP‐3, exhibited much higher load‐carrying capacity, reducing friction and anti‐wear property than that observed on PAO‐20.